1989
DOI: 10.1109/16.19949
|View full text |Cite
|
Sign up to set email alerts
|

Thin-film transistors with sputtered CdSe as semiconductor

Abstract: Thin-film transistors have been fabricated on a CdSe stoichiometric semiconductor film deposited by using RF magnetron sputtering from a CdSe target. The main features and the characteristic data of such transitions realized are presented. The threshold voltage Vt=4 V, the field-effect mobility μ=45 cm2 /V-s, and the switching current ratio ION/IOFF=5×107. These values are comparable to those obtained for similar devices fabricated on evaporated CdSe film

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…CdSe thin films have been prepared by various film deposition techniques such as sputtering (Moersch et al, 1989), MOCVD (Chae et al, 2006), electron beam evaporation (Murali et al, 2008), photoelectrochemical (Pawar et al, 2006), and chemical bath deposition (CBD) method which is found to be cheap, low deposition temperature and simple way to deposit large area thin film 2005), (Ezema and Osuji, 2007) and (Elahi and Ghobad, 2008).…”
Section: ‫ــــــــــــــــــــــــــــــــــــــــــــــــــــــ‬ Intmentioning
confidence: 99%
“…CdSe thin films have been prepared by various film deposition techniques such as sputtering (Moersch et al, 1989), MOCVD (Chae et al, 2006), electron beam evaporation (Murali et al, 2008), photoelectrochemical (Pawar et al, 2006), and chemical bath deposition (CBD) method which is found to be cheap, low deposition temperature and simple way to deposit large area thin film 2005), (Ezema and Osuji, 2007) and (Elahi and Ghobad, 2008).…”
Section: ‫ــــــــــــــــــــــــــــــــــــــــــــــــــــــ‬ Intmentioning
confidence: 99%
“…The TFTs had the usual inverted staggered configuration (see, for example, [6,7]) and were fabricated on n + -Si<100> wafers on which was grown a 300 nm thick thermal gate oxide. The substrates were heated in vacuum in the CdSe deposition chamber at 200 o C for 10 minutes to desorb residual water from the surface and then cooled to the deposition temperature of 70 o C. CdSe (99.995% pure) was deposited to a thick- …”
Section: Device Description and Experimental Detailsmentioning
confidence: 99%
“…Cadmium selenide (CdSe) is an important member of II-VI group of binary compounds which has many applications like high-efficiency thin film transistors, [1,2] solar cells, [3,4] photoconductors [5] and gas sensors. [6,7] In order to improve the performance of the devices, key attention has been given in recent years to study the physical properties of CdSe thin films.…”
Section: Introductionmentioning
confidence: 99%